Comparative analysis of different prophylactic methods for roughness of primary tooth enamel - Fava, Marcelo [UNESP]; Frascino, Alexandre Viana; Balducci, Ivan [UNESP]; Ramos, Carolina Judica [UNESP] (Editora Cubo, 2018)
Objective: The purpose of this study was to comparatively evaluate quantitative effects of three different prophylactic methods of surface polishing treatments for primary teeth compared to a standardized control group. Material and Methods: 48 naturally exfoliated primary teeth were selected and randomly assigned into four groups: Control Group – teeth receiving only enamel standardization treatment with polishing disc to reduce natural enamel; Group I – teeth receiving superficial enamel standardization treatment followed by polishing with a mixture of water and pumice; Group II – teeth receiving enamel standardization treatment followed by prophylaxis with paste (Herjos-F, Vigodent S/A Indústria e Comércio, Rio de Janeiro, Brazil); and Group III – teeth receiving enamel standardization treatment followed by sodium bicarbonate spray (Profi II Ceramic, Dabi Atlante Indústrias Médico-Odontológicas Ltda, Ribeirão Preto, Brazil). All the procedures were performed by the same operator and the samples were rinsed and stored in distilled water. Comparative assessment of the enamel surface roughness between experimental groups and control group was performed by using a surface profilometer (Mitutoyo SJ400). Results: The results of this study were statistically analysed by using Minitab statistical software (version 17.1.0, 2013). The use of pumice and water led to significantly rougher surfaces than in other groups (i.e. Group I: 1.22 Ra; Group II 0.38 Ra; Group III: 1.01 Ra). Conclusion: Based on this study, one can conclude that use of pumice and water resulted in increased enamel surface roughness in comparison to the surface treatment with bicarbonate spray and prophylaxis paste.
Análise comparativa de diferentes métodos profiláticos sobre a rugosidade do esmalte em dentes decíduos
Keywords: Dental enamel; Dental prophylaxis; Enamel roughness; Jet abrasive system; Primary teeth